CONSTITUTIONAL COMPLAINT DAN CONSTITUTIONAL QUESTION DAN PERLINDUNGAN HAK-HAK KONSTITUSIONAL WARGA NEGARA - Hamdan Zoelva (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
The 1945 Constitution gives limitative authority to the Constitutional Court only to review of laws against the constitution, adjudicate dispute over state institution whose authorities are mandate by constitution, adjudicate dispute on the result of general election, dissolution of political parties and obliged to decide upon DPR’s opinion in the case of the impeachment of the President. In practice, many of the constitutional issues can not be resolved by the Constitutional Court because it explicitly doesn’t include the authority of the Constitutional Court, for example, the adjudication of the constitutional complaint and the constitutional question. Both of these issues are not easily resolved by the Court outside of the Constitutional Court. The main issue to be analyzed in this paper is the possibility that the Constitutional Court may adjudicate constitutional complaint and constitutional question. By using the normative approach, comparative study of several other countries as well as theoretical studies on the functions of the Constitutional Court in constitutional democracies states, this paper analyzes the possibility of the Indonesian Constitutional Court may adjudicate constitutional complaint and the constitutional question.